Analysis of the snail Biomphalaria glabrata (Say, 1818) and identification of infected areas in the lagoon of Retiro, Junqueiro/AL/Análise do caramujo Biomphalaria glabrata (Say, 1818) e identificação de áreas infectadas na lagoa do Retiro, Junqueiro/AL - José Danilo da Silva; José Danilo da Silva; Juliana Ferreira dos Santos; Cicera Maria Alencar do Nascimento; Mabel Alencar do Nascimento Rocha (Universidade Estadual de Alagoas, 2020)
Schistosomiasis Mansoni is endemic in approximately 76 countries and it currently affects 8 million Brazilian posing a serious threat to our country health system and population. The parasite Schistosoma Mansoni has the Biomphalaria Mollusc as its intermediate host and their infected larvae, is responsible for transmitting the disease to the population when they are released in the water. People in contact with water infested by larvae are prone to catch this dangerous disease. Our study was conducted in three different areas of lagoon do Retiro, nearby the city of Junqueiro- Al, Brazil. Molluscs were collected with the help of a special sieve, then kept in plastic containers identified by the area and sent to the State University of Alagoas( Uneal) laboratory, in Campus 1. There they were isolated and studied in a petri dish containing 10 ml of dechlorinated water and exposed to a 40 W incandescent lamp. For the molluscs that did not promptly test positive for the Schistosoma Mansoni, the exposure was repeated in the space if 7, 15 and 30 days, in order to rule out the possibility of infection. Out of the 3 areas studied in 2018 one tested positive with a total of 8 infected molluscs. The study therefore proved the lagoon is not safe to swim, bathe, or have its water used by the population and the public heath departament should alert the local population about this danger and health risc.